The Cambridge encyclopedia of human evolution - Jones, Steve 1944-; Martin, R. D. (Robert D.) 1942-; Pilbeam, David R. (Cambridge [England] Cambridge University Press, 1992)
Introduction to human evolution with coverage ranging from genetics to demography and disease. Includes diagrams, maps, and photographs
Includes bibliographical references (p. 473-486) and index
Keywords: Human evolution -- Encyclopedias; Biological Evolution -- Encyclopedias -- English; Hominidae -- Encyclopedias -- English